Response time analysis of hard real-time tasks sharing software transactional memory data under fully partitioned scheduling - Barros, António (2016)
11th IEEE International Symposium on Industrial Embedded Systems (SIES 2016). 23 to 25, May, 2016. Krakow, Poland.